Regulating Sperm Donation in Indonesian IVF: A Maqashid al-Shariah Perspective - Cut Zatihulwani; Muhsan Syarifuddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
The rapid development of assisted reproductive technologies has expanded the application of in vitro fertilization (IVF), including sperm donation, a practice prohibited under Indonesian positive law and Islamic legal principles. Despite these legal prohibitions, limited research has examined whether the existing regulatory framework effectively prevents sperm donation practices involving Indonesian citizens, particularly from the perspective of Maqāṣid al-Sharīʿah. This study aims to evaluate the effectiveness of Indonesia's sperm donor regulations in IVF practices through the lens of Maqāṣid al-Sharīʿah. The research employs a normative legal method using statutory, conceptual, and case-based approaches by analyzing legislation, Islamic legal opinions, judicial decisions, and relevant empirical evidence. Legal materials were examined through descriptive, comparative, and analytical techniques to assess the relationship between regulatory norms and their implementation. The findings reveal that although sperm donation is expressly prohibited under both Indonesian law and Islamic jurisprudence, regulatory effectiveness cannot be measured solely by the existence of legal restrictions because such practices continue through domestic and cross-border reproductive services involving Indonesian citizens. The study concludes that effective regulation requires not only legal prohibition but also consistent enforcement, institutional supervision, and cross-border legal cooperation to safeguard lineage (ḥifẓ al-nasl), religion (ḥifẓ al-dīn), human dignity (ḥifẓ al-ʿirḍ), and public welfare (maṣlaḥah). Academically, this study contributes by developing Maqāṣid al-Sharīʿah as an evaluative framework for measuring regulatory effectiveness, thereby extending its application beyond normative legal justification to the assessment of reproductive governance and the gap between legal norms and social practice.